A plastid DNA phylogeny of the genus Acacia Miller (Acacieae, Leguminoseae) - Robinson, J; Harris, S (2000)
Past classifications of the tribe Acacieae Rchb. are outlined and the confusion concerning the relationships of the three subgenera of Acacia Mill. are highlighted. A plastid DNA analysis of Acacieae shows that the genus Acacia is not monophyletic. Furthermore subgenera Acacia Vassal and Aculeiferum Vassal are sister taxa and neither appear closely related to subgenus Phyllodineae (DC.) Ser. Subgenera Acacia and Aculeiferum form a clade that is basal to a well-supported clade consisting of tribe Ingeae Benth. taxa, Faidherbia albida (Del.) A. Chev. and subgenus Phyllodineae. The series of relationships suggested by the cpDNA data contradicts previous investigations of the tribe. Possible explanations of this conflict are explored, and the taxonomic implications of the plastid DNA data set are considered. (C) 2000 The Linnean Society of London.